Mechanism Design and Simulation Analysis of Obstacle Surmounting Multi-leg Robot - Jun Liu; Chengmin Wang; Feng Wang (Jixie chuandong)
A kind of obstacle surmounting multi-leg robot is designed，the robot has the characteristics of fast moving speed and strong obstacle surmounting. Leg mechanism design is one of the important factors that affect the motion characteristics of multi-leg robot. A new kind of leg mechanism of multi-leg robot is designed based on crank rocker principle. In order to ensure that the center of gravity does not change in the process of robot moving，the tread curve of tread is designed by Matlab software，and the influence rules of different size parameters of leg mechanism on tread curve，horizontal velocity and acceleration of the contact point of single tread and ground are analyzed. At the same，the auxiliary climbing mechanism of the multi-leg robot is designed，and the work flow of the multi-leg robot climbing over obstacles is analyzed. Finally，the feasibility of the mechanism design of obstacle surmounting multi-leg robot is verified by virtual prototype motion simulation and physical prototype test.